Coral bleaching assessment in the selected reefs of Taklong Island national Marine Reserve, Nueva Valencia, Guimaras. - Ygona, Hurby L.
Incidents of coral bleaching have been recurrently increasing over the past years. In 2017, the 3rd global bleaching event affected a lot of corals worldwide. This was due to the recurrent El Niño formations in the year 2015 and 2016, and the subsequent La Niña formation that prolonged the bleaching event. Thus, the study was done to supplement and contribute to the post-bleaching assessments, specifically on the Philippine corals. The main goal of the study was to determine the reef health status in 3 selected reefs of Taklong Island National Marine Reserve (TINMR),. Nueva Valencia, Guimaras. The specific aims were: 1) to identify coral morphology and taxonomy, 2) to assess reef health based on the degree of bleaching condition by coral morphology and by taxonomy using Coral Health ChartTM, and 3) to assess reef based on live coral cover, mortality indices, algae coverage, and sand coverage (Zamani et al., 2011). These were atleast 11 hard and soft coral genera observed in the 3 selected reef sites in TINMR Guimaras, namely Porites, Pocillopora, Favia, Acropora, PAvona, Favites, Montipora, Clavularia, Seriatopora, Sarcopython were more susceptible to bleaching while Montipora was least susceptible. In terms of coral morphology, soft corals were most susceptible to bleaching, followed by plate corals; whereas branching and boulder corals were least susceptible. The reefs can be classified as ?healthy? with respect to coral bleaching status. However, coral bleaching aside, the reef health was poor due to the alarming rate of coral mortality, with values ranging from 0.206 to 0.247. The results provide a useful prognosis to the reefs in TINMR for reef management and restoration actions that should improve the resilience of these reefs and protect theme from disturbances caused by the El Niño.